Study on influencing factors of residents travel mode choice for Ho Chi Minh city - Nguyen, Anh Tuan; Zhou, WenHui; Yu, JianJun (Vietnam Journal of Science and Technology, 2015)
ABSTRACT Considering the travel character of travelers, attribute of travelers and the original attribute of transportation modes, and searching the travel cost and travel time of private cars and public buses, this paper sets up a logistic model to investigate the travelers’ behavior in Ho Chi Minh city. Specifically, the significance level used in this model is 0.05. Through this model, it shows that the major factors affecting the behavior of traveler are travel distance, the difference of travel cost between cars and buses, the cost of congestion, the parking fee of cars, the difference of time between cars and buses, and the time for travelers to reach the bus stops on foot. Furthermore, this model indicates that by increasing the fuel fee, parking fee and congestion fee, less travelers would choose cars as their travel tool.